2019
DOI: 10.14356/kona.2019013
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Interaction Forces between Surfaces in Liquids Using Atomic Force Microscopy

Abstract: The stability of particle suspensions, which is important in numerous industrial processes, is generally dominated by the interaction forces between the suspended particles. Understanding the interaction forces between surfaces in liquids is therefore fundamentally important in order to evaluate and control how particulates, including fluid droplets in emulsions and air bubbles in foams, behave in various systems. The invention of the surface force apparatus (SFA) enabled the direct measurement of interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…However, if so desired, more sophisticated AFM force measurements are capable of discerning the identity of the liquid. Immersed liquids adjacent to solid surfaces exhibit either a short-ranged (∼nm) repulsion or attraction, , while ionic liquids with relatively large molecules can present discrete steps over a distance of several nanometers. …”
mentioning
confidence: 99%
“…However, if so desired, more sophisticated AFM force measurements are capable of discerning the identity of the liquid. Immersed liquids adjacent to solid surfaces exhibit either a short-ranged (∼nm) repulsion or attraction, , while ionic liquids with relatively large molecules can present discrete steps over a distance of several nanometers. …”
mentioning
confidence: 99%
“…The ionic strength of a fluid is somewhat an unknown. However, works have indicated that for deionized water, typical ionic strength values are measured of the order of I = 1 mol/m 3 46 . This value is assumed for all the fluids used.…”
Section: Methodsmentioning
confidence: 99%
“…By AFM, it is not possible to record the entire interaction potential between tip and object, since the cantilever imposes an external force that makes the system "jump to contact" at a certain distance above the surface. 199 However, the AFM can nevertheless help to identify the different forces, if individual parameters (e.g., salt concentration or wettability) can be varied separately. 200 Indirectly, by recording the topography of a thin polymer film, AFM helped to reveal the effective interface potential of the system air/thin polymer film/silicon wafer, which can be described by a Lennard-Jones-type potential in the appropriate geometry (two flat semi-infinite interfaces interact) possible: 201,202 at temperatures above the glass transition temperature (here T > 480 K), the thin polystyrene film can dewet spinodally under certain conditions off a Si wafer.…”
Section: Insights Into Intermolecular Interactions By Surface Forces ...mentioning
confidence: 99%